(untitled) (Pesquisa Odontológica Brasileira, 2000)
The present work evaluated the effect of low doses of X-irradiation on the repairing process of sutured and nonsutured skin wounds in rats. For that, rats underwent a surgical proceedure, in which a 20 x 5-millimeter rectangular wound approximately 2-millimeter-deep was made in the dorsal region of each animal, and were divided in four groups: nonirradiated nonsutured; irradiated nonsutured ; nonirradiated sutured and irradiated sutured. The animals under irradiation were protected, during exposure, with a 2-millimeter-thick lead apron in such a way that only the incision was irradiated. Each animal was submitted to 18 seconds of exposure, undergoing a total of 7.4 rads. The evaluation of the effects of X-rays on the repairing process was carried out through microscopic observation by means of hematoxylin-eosin staining for morphological evaluation, and silver impregnation under polarized light for the observation of collagen synthesis. The results have shown that X-irradiation has caused delay in the repairing process, but it did not stop its development. The irradiated nonsutured group was considered to show the greater delay when compared with the other groups.